Tourists' tourism experiences and their revisit intentions to Skyrides Festivals Park, Putrajaya / Mazlina Mahdzar and Arni Abdul Gani - Mahdzar, Mazlina; Abdul Gani, Arni (UiTM Cawangan Johor, 2019)
Tourism industry is an important economic generating income for a country. Theme parks are one of the tourism products that motivate people to travel to a particular destination and one of the important generators in tourism demand. This study aims to examine the relationship linking tourists' memorable tourism experience attributes and their revisit intentions to theme parks. Using convenience sampling, a total of 370 survey questionnaires were distributed to respondents after their visit to Skyrides Festivals Park in Putrajaya, and the data were used for data analysis. Regression results revealed that three Memorable Tourism Experience attributes have significant relationships with tourists' revisit intention. They are meaningfulness experience, novelty experience and refreshing experience of these three attributes, novelty proves to have the most significant impact on tourists' revisit intentions.